2014
DOI: 10.33119/gn/100877
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Polish IPO Firms: Size and Profitability Effect

Abstract: The study investigates the price behavior after initial public offerings (IPOs) listed on the Warsaw Stock Exchange from 2004 to 2009. It focuses on possible explanations for the IPO phenomenon within the context of Poland and provides evidence on the relation between both the company size and profitability and the aftermarket price performance. The study aims to answer three questions. First, whether we could observe the short -term underpricing and the long -term underperformance of Polish IPOs, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…Aussenegg [57], Jelic and Briston [58], Lyn and Zychowicz [59] discussed it for the first stage of the equity market stage, and mainly focused on privatization issues. More recent studies on IPOs in Poland include Jewartowski and Lizińska [60], Czapiewski and Lizińska [61] and Lizińska and Czapiewski [62]. All of them reported that Polish IPOs experienced negative buy-and-hold abnormal returns, not only in comparison to the market approximated with the index, but also for one-dimensional benchmarks based on size, book-to-market, and two-dimensional benchmarks, both with equal-and value-weighting.…”
Section: Earnings Quality Around Going Public: the Existing Evidencementioning
confidence: 99%
“…Aussenegg [57], Jelic and Briston [58], Lyn and Zychowicz [59] discussed it for the first stage of the equity market stage, and mainly focused on privatization issues. More recent studies on IPOs in Poland include Jewartowski and Lizińska [60], Czapiewski and Lizińska [61] and Lizińska and Czapiewski [62]. All of them reported that Polish IPOs experienced negative buy-and-hold abnormal returns, not only in comparison to the market approximated with the index, but also for one-dimensional benchmarks based on size, book-to-market, and two-dimensional benchmarks, both with equal-and value-weighting.…”
Section: Earnings Quality Around Going Public: the Existing Evidencementioning
confidence: 99%
“…Profitability (ROA): We measured as net profit to total assets as in previous studies of IPO success (Brycz et al, 2017). Size (LOGMcap): Previous research indicates that information asymmetry is less likely to exist for larger firms (Lizińska and Czapiewski, 2014). Then the log of the firm's market capitalization at the end-year IPO is used to control the size effect.…”
Section: Methodsmentioning
confidence: 99%
“…Investors' behavior on the IPO market is often explained by the phenomenon of information asymmetry (Ljungqvist, 2007). As Lizińska and Czapiewski (2014) write, market investors and security analysts usually try to decrease the uncertainty level by observing company financial situation. In order to do it, they analyze certain financial ratios with the assumption that reported financial relations are reliable and able to reveal some information about the company real situation and prospects for the future.…”
Section: Ipo Success and Its Factorsmentioning
confidence: 99%
“…Lyn and Zychowicz (2003) found no significant relationship between profitability and short-term IPO underpricing. Lizińska and Czapiewski (2014) observed that short-term IPO returns in Poland were much higher for more profitable firms. However, the relationship between around-the-IPO profitability was not so evident for long-term abnormal performance measured with BHARs as it was not robust to alternative methods.…”
Section: Related Literaturementioning
confidence: 99%